Early HIV Diagnosis Leads to Significantly Decreased Costs in the First 2 Years of HIV Care in an Urban Charity Hospital in New Orleans. (November 2017) - Halperin, Jason; Katz, Morgan; Pathmanathan, Ishani; Myers, Leann; Van Sickels, Nicholas; Seal, Paula Sereebutra; Richey, Lauren E.
We undertook a retrospective cohort study of patients with a positive HIV test in the emergency department who were then linked to care. Inpatient, outpatient, and emergency costs were collected for the first 2 years after HIV diagnosis. Fifty-six patients met the inclusion criteria; they were predominantly uninsured (73%) and African American (89%). The median total cost for a newly diagnosed patient over the first 2 years was US36 808, driven predominantly by outpatient costs of US17 512. Median inpatient and total costs were significantly different between the lowest (<200 cells/mm 3 ) and highest (>499 cells/mm 3 ) CD4 count categories (US21 878 vs US6607, P <.05; US61 378 vs US18 837, P <.05, respectively). Total costs were significantly different between viral load categories <100 000 HIV-RNA copies/mL and ≥100 000 HIV-RNA copies/mL (US28 219 vs US49 482, P <.05). Costs were significantly lower among patients diagnosed earlier in their disease. Decreased cost is another factor supporting early diagnosis and linkage to care for patients with HIV.